2019
DOI: 10.1002/admi.201900535
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Stratifying Silicone Coating with Nonleaching Antifoulant for Marine Anti‐Biofouling

Abstract: dynamic surfaces, [4] polymethacrylate bearing ferrocenyl groups, [5] amphiphilic copolymers, [6] liquid-infused slippery surfaces, [7] surface-deforming materials, [8] enzyme containing coatings, [9] and so on. Among them, silicone-based FRCs with excellent fouling release ability have gained considerable attention because it is environment-friendly and has drag reducing ability. [10] The fouling release ability of silicone elastomers arises from its low surface energy and low elastic modulus. [11] The latt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(30 citation statements)
references
References 42 publications
2
24
0
Order By: Relevance
“…Compared with PEG or zwitterion‐modified polymer‐based and hybrid antifouling systems, [ 3–9,20 ] the results show our material exhibits similarly excellent antifouling performance but much higher hardness, modulus, and adhesion strength. For hybrid coatings designed for foldable displays, previous Zr containing materials or flexible hard hybrid coatings exhibit superior mechanical properties but with no antismudge or antimicrobial functions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with PEG or zwitterion‐modified polymer‐based and hybrid antifouling systems, [ 3–9,20 ] the results show our material exhibits similarly excellent antifouling performance but much higher hardness, modulus, and adhesion strength. For hybrid coatings designed for foldable displays, previous Zr containing materials or flexible hard hybrid coatings exhibit superior mechanical properties but with no antismudge or antimicrobial functions.…”
Section: Resultsmentioning
confidence: 99%
“…Today, eco‐friendly yet high antifouling performance antifouling coatings are expected. [ 2 ] Accordingly, siloxane‐based fouling‐release coatings, [ 3 ] antifouling copolymers, [ 4 ] and polymer brushes [ 5 ] have been prepared to inhibit biofouling. However, these polymer‐based materials often exhibit poor mechanical properties, and they are readily destroyed and even peeled from the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Polymer surface-active additives are used to modify and opportunely modulate the surface properties of the polymer matrix into which they are incorporated—either physically dispersed [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ] or chemically linked [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. In fact, by taking advantage of the ability of the additive to selectively segregate at the surface of a polymer film, the wettability properties are commonly changed [ 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this way, many coating properties dictated by the surface layer, such as tackiness, hardness, water resistance, and dirt pick-up, can be designed and optimized separately from the bulk materials. [8][9][10][11][12] However, conventional coating systems do not self-stratify. Previous studies demonstrated that self-stratification will only happen for polymers of specific chemistry or particle mixtures of certain size ratios when a coating suspension dries.…”
Section: Introductionmentioning
confidence: 99%